2022
DOI: 10.1021/acs.jpca.2c04547
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Kinetic Studies of the Ozonolysis of Selected Allyl Sulfides (H2C═CHCH2SR, R = CH3, CH3CH2): The Effect of Nascent OH Radicals

Abstract: Rate coefficients of the O 3 -initiated oxidation of allyl methyl sulfide (H 2 C�CHCH 2 SCH 3 , AMS) and allyl ethyl sulfide (H 2 C�CHCH 2 SCH 2 CH 3 , AES) were determined at atmospheric conditions by "in situ" FTIR. The relative kinetic experiments were performed using methylcyclohexane (McH) and carbon monoxide (CO) as nascent OH radical scavengers and in the absence of any scavenger, to determine the impact that the formation of OH radicals has on the rate coefficients. In the absence of scavengers, values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Nevertheless, many single-reference (SR) approaches to O 3 modeling have been reported. ,, Errors in these predictions can be substantial. As Wheeler et al have noted, generally respectable SR methodologies predict barrier heights with discrepancies in excess of 10 kcal mol –1 for small systems like C 2 H 2 and C 2 H 4 , and even the CCSD­(T) (coupled-cluster with single, double, and perturbative triple excitations) method gives unsatisfactory results .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, many single-reference (SR) approaches to O 3 modeling have been reported. ,, Errors in these predictions can be substantial. As Wheeler et al have noted, generally respectable SR methodologies predict barrier heights with discrepancies in excess of 10 kcal mol –1 for small systems like C 2 H 2 and C 2 H 4 , and even the CCSD­(T) (coupled-cluster with single, double, and perturbative triple excitations) method gives unsatisfactory results .…”
Section: Introductionmentioning
confidence: 99%
“…46,91 Nevertheless, many single-reference (SR) approaches to O 3 modeling have been reported. 47,59,[92][93][94][95][96][97][98][99][100][101] Errors in these predictions can be substantial. As Wheeler et al have noted, generally respectable SR methodologies predict barrier heights with discrepancies in excess of 10 kcal mol −1 for small systems like C 2 H 2 and C 2 H 4 , and even the generally reliable CCSD(T) (coupled-cluster with single, double, and perturbative triple excitations) method gives unsatisfactory results.…”
Section: Modeling Ozone Chemistrymentioning
confidence: 99%
“…Initiation of the VOC oxidation process is primarily driven by the sunlight-derived OH radical but also via reactions involving other oxidants. Papers in this virtual special issue include studies of the initiation reactions of VOC species by OH, Cl, O 3 , , NO 3 , and HCO, as well as by direct photolysis . Chamber studies, in which the products of a VOC oxidation process are identified and quantified, are also prevalent; two studies quantify the formation of secondary organic aerosol (SOA) in the reaction of OH or NO 3 with monoterpenes, , while a combined experimental/theoretical study shows that methylmethanimine oxidation via the OH radical is unlikely to compete with atmospheric hydrolysis of this species .…”
mentioning
confidence: 99%